Assessment of the liver transplantation in the State of Santa Catarina from August, 2002 to January, 2008. - Nogara, Marcelo Augusto Scheidemantel; Wiederkher, Julio; Benghi, Renan André Cicatto; Zalli, Marcelo; Helena, Ernani Tiaraju de Santa (Brazilian Journal of Transplantation, 2009)
Purpose: To assess liver transplants in the State of Santa Catarina in the period from August 2002 to January 2008. Methods: This is a retrospective cohort in which the inclusion criterion was patient submitted to liver transplantation at least one year before. The study was conducted by collecting data from charts of patients during their hospital stay for the transplantation. It was searched epidemiological data (age, gender, city of origin, indications for the liver transplantation), the pre-transplantation MELD score and Child-Pugh classification, post-transplantation complications, causes for the death and evolution of transplantation (occurrence of re-transplantation, survival, hospital and ICU stay). Data collection was conducted from October 2008 to February 2009. Results: The mean age attained in our study was 50.08 years. Among the transplants, 77% were male. As to the origin, 26.2% were from Blumenau, 66.3% came from other cities of the State of Santa Catarina, and 7.4% of patients lived in other States. From 187 patients who underwent liver transplantation, 48.7% were classified Child-Pugh B, and 35.8% were classified C; only 15.5% were classified Child-Pugh A. When assessing the MELD, 39.6% were classified as less than 18, and 60.4% of patients had MELD equal or higher than 18. The most prevalent cause for the liver transplantation indication was cirrhosis (65.7%). As to the complications, it was observed that some patients had more than one. Infections were the most prevalent with 135 cases, followed by pulmonary complications with 43 cases, and clinical complications in 33 cases. The mean hospital and ICU stay was 14.6 and 4.8 days, respectively. since the beginning of THE transplantation Up to the end of the study the fatality was 33.7%, representing 50.8% of septic shock cases. Conclusion: The study showed that data were mostly congruent with those reported in the literature, proving that this is a service that has several good results and a significant data improvement related to previous publications.